HUBUNGAN ANTARA KEHARMONISAN KELUARGA DENGAN PERILAKU AGRESIF PADA SISWA MADRASAH ALIYAH RAUDLATUSSHIBYAN NW BELENCONG TAHUN PELAJARAN 2019/2020 - Ahmad, Hariadi; Wurru, Lidya Lali; Maharani, Jessica Festy (Realita : Jurnal Bimbingan dan Konseling, 2021)
Abstract. Marriage is designed to form a harmonious and eternal family in accordance with Law number 1 of 1974. Therefore it is the responsibility of parents in teaching various knowledge, value and norm as well as role model in behavior to children. It was found that children with disharmony family background will experience the disorder of personality, emotional, antisocial and behavioral disorder (delinquent). The purpose of this study was to know the relationship between family harmony with aggressive behavior in students of the Belencong Aliyah Raudlatushibyan NW Madrasah in Academic Year of 2019/2020. Family harmony is characterized by a form of two-way communication, mutual respect for opinion, mutual love and the attitude of parents who protect children. Aggressive behavior intended in this research is in the form of physical, psychological, verbal and non-verbal aggressive The design of this study used quantitative research that is a causal relationship. The sample in this study were 21 students from disharmony families. Data collection technique using the questionnaire method as the main method, observation, interview and documentation as a complementary method. By the result of data analysis using statistical method with Product Moment analysis showed that the value of r-count <r-table was 0.871 <1.729 then the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted at a significance level of 5% so that it can be interpreted that there is a Relationship Between Family Harmony with Aggressive Behavior Students of the Belencong Aliyah Raudlatushibyan Madrasah in Academic Year ofÂ  2019/2020. Key word: harmony family, aggressive.